Global proteomic analysis of tumor cells and stromal from Canine mammary tumors: a potential model for comparative oncology - Lopes, Adália Freitas de Oliveira (2023)
The present dissertation had two objectives: 1) to discuss the value of specific analyses in CMT using transcriptomics and proteomics for comparative oncology through a literature review; 2) to determine a comparative and quantitative analysis of proteins from CMT using the bottomup proteomics approach. In chapter 1 we discussed the importance of using bitches with spontaneous mammary tumors as an animal model for HBC. The study of CMT can strongly contribute to the understanding of the disease course and contribute to the discovery of not only diagnostic but also prognostic and therapeutic biomarkers of breast cancer. The expression of tumor genes and proteins through the use of analyses such as transcriptomics and proteomics of tumor cells present in TMC have provided a wealth of data on gene expression, but the tumor stroma lacks studies. In chapter 2 we searched for candidate biomarkers of breast tumor status using a proteomic approach. We compared protein expression of canine mammary tumors (CMT) and normal mammary glands tissues (NT). Tissue samples (5 TMC and 5 NG) obtained from post-mortem female dogs from the Zoonosis Control Center (CCZ) were collected. The samples were divided into two portions. One portion was frozen and stored at -17◦C until used for proteomic analysis and the other portion followed standard biopsy procedures and was stored at room temperature. Benign mixed tumors (n=2), inflammatory carcinoma (n=1), complex adenomas (n=2), NT (n=5) were selected for shotgun proteomic approach. Peptide spectrum search was performed using Progenesis v4.2 which allowed the identification of an average of 945 proteins, 136 of which were overexpressed proteins in CMT. Most of these overexpressed proteins were involved in biological processes related to tumor process. In the study, FN1, FGD3, TNN, ACAN, and ATP5F1B as the most abundant proteins among TMC overexpressed proteins. Thus, through molecular characterization of CMT and bioinformatics analyses, we describe key proteins that may be further useful in validating biomarkers for both human and canine mammary cancer.